(3cJGH GdHdGZIs - (3eLghds
(3ChdgG (B:s
... (3hHjfgeG Cj hHjf GdWQajf eQGJH cKjQI eJaGhJI HYVgG CYdi ef HYV HMSH JaGhJ GdebGeGJ hQYGjI GdGYJHGQGJ hGdHYO ef CSHGH GdENdGd HGdaUGMI hJJHYgG Cj HdGZI GdcdGe jhQK GdcdGe MSfG haj bhdg JJHYgG GTGQI Edi JMSjf gPP GdhLhg EfeG JYO eMSfI HYPQ(B...s
(3BNQgG (B:s
... (3dCf GdeeGKdI dG JJMbb EdG aj GdLGfHjf EP ef eGKd GdTjA abO eG(B.. (3PdcM GdTjA ajdRe faSg dGfg eKd eKdg hbO fai hbjd GdcGa RGFOI dCf GdeQGO HeKdg gh faSg aGdJbOjQ djS cgh TjA hbjd GdeKd RGFO LjA Hg djUM ONhd GdcGa Ydi GdeVeQ (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdHdGZIs